Expanding the Applicability of Poly(Ionic Liquids) in Solid Phase Microextraction: Pyrrolidinium Coatings - David J. S. Patinha (Materials, 2017)
Crosslinked pyrrolidinium-based poly(ionic liquids) (Pyrr-PILs) were synthesized through a fast, simple, and solventless photopolymerization scheme, and tested as solid phase microextraction (SPME) sorbents. A series of Pyrr-PILs bearing three different alkyl side chain lengths with two, eight, and fourteen carbons was prepared, characterized, and homogeneously coated on a steel wire by using a very simple procedure. The resulting coatings showed a high thermal stability, with decomposition temperatures above 350 °C, excellent film stability, and lifetime of over 100 injections. The performance of these PIL-based SPME fibers was evaluated using a mixture of eleven organic compounds with different molar volumes and chemical functionalities (alcohols, ketones, and monoterpenes). The Pyrr-PIL fibers were obtained as dense film coatings, with 67 μm thickness, with an overall sorption increase of 90% and 55% as compared to commercial fibers of Polyacrylate (85 μm) (PA85) and Polydimethylsiloxane (7 μm) (PDMS7) coatings, respectively. A urine sample doped with the sample mixture was used to study the matrix effect and establish relative recoveries, which ranged from 60.2% to 104.1%.